Secretory leukocyte protease inhibitor (SLPI) promotes cholangiocarcinoma progression via inflammation-associated and vasculogenic mechanisms - Kangsadan Chueajedton; Chaiwat Chueaiphuk; Jeranan Inpad; Sarawut Kumphune; Worasak Kaewkong; Damratsamon Surangkul; Kanlayanee Sawanyawisuth; Ubon Cha’on; Suchada Phimsen (PLoS ONE, 2026)
Cholangiocarcinoma (CCA) is a lethal cancer associated with chronic inflammation caused by Opisthorchis viverrini infection, with high prevalence in Thailand. Secretory leukocyte protease inhibitor (SLPI), a serine protease inhibitor involved in inflammation, has recently been identified as an oncogenic factor in several malignancies. However, its role in CCA remains unclear. Here, we demonstrate that SLPI is significantly upregulated during CCA development in both human and hamster-induced tissues. Higher SLPI expression was correlated with poor patient survival based on bioinformatic analyses. SLPI was elevated in highly metastatic CCA cell lines and further inducible by IL-6 stimulation. Overexpression of SLPI enhanced tumorigenic properties, including proliferation, migration, invasion, and in vivo tumor growth. SLPI also increased the activity of matrix metalloproteinases (MMP-2 and MMP-9), promoting metastatic potential. While conditioned media from SLPI-overexpressing cells did not affect angiogenesis, these cells promoted vasculogenic mimicry, with increased expression of VEGFA and VE-cadherin, and decreased N-cadherin. These findings suggest that SLPI promotes cholangiocarcinoma progression through inflammation-associated and vasculogenic mechanisms, highlighting its potential as a candidate molecular target for therapeutic intervention.